2013
DOI: 10.1002/pbc.24533
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in childhood cancer: A society for pediatric radiology and children's oncology group joint task force report

Abstract: Contemporary medical imaging is a cornerstone of care for children with cancer. As 5-year survival rates for children with cancer exceed 80%, imaging technologies have evolved in parallel to include a wide array of modalities. Here, we overview the risks and benefits associated with commonly used imaging modalities and survey the current landscape of medical imaging for children with cancer. We find evidence-based imaging guidelines to assist in protocol development and to guide decision-making for optimal pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 87 publications
(113 reference statements)
0
42
0
Order By: Relevance
“…In addition, our study and others have supported the importance of providing rationale to limit the use of certain scans in subsets of patients. Recent pediatric oncology specific publications from Radiology societies and COG have highlighted additional issues, such as surveillance‐associated cost and psychological stress, and the need to increase availability of lower dose CT technology . These reports suggest that there is currently little evidence to guide optimal frequency and modality of scans, or to determine when to limit imaging to subgroups depending on tumor locations and/or relapse risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our study and others have supported the importance of providing rationale to limit the use of certain scans in subsets of patients. Recent pediatric oncology specific publications from Radiology societies and COG have highlighted additional issues, such as surveillance‐associated cost and psychological stress, and the need to increase availability of lower dose CT technology . These reports suggest that there is currently little evidence to guide optimal frequency and modality of scans, or to determine when to limit imaging to subgroups depending on tumor locations and/or relapse risk.…”
Section: Discussionmentioning
confidence: 99%
“…Recent pediatric oncology specific publications from Radiology societies and COG have highlighted additional issues, such as surveillance-associated cost and psychological stress, and the need to increase availability of lower dose CT technology. 36,37 These reports suggest that there is currently little evidence to guide optimal frequency and modality of scans, or to determine when to limit imaging to subgroups depending on tumor locations and/or relapse risk. 22 We also found that in addition to history/symptoms and UCats, MIBG scans detected the majority of recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable debate surrounding the utility of surveillance imaging in patients with pediatric cancer . For high‐risk neuroblastoma, surveillance imaging practices vary among institutions and the use of routine chest CT as an initial staging and surveillance tool is debatable.…”
Section: Discussionmentioning
confidence: 99%
“…While the implemented changes in imaging protocols have been effective at reducing radiation exposure, clinicians must diligently evaluate the risks and benefits of surveillance imaging. There has been considerable debate surrounding the utility of surveillance imaging in patients with pediatric cancer [30][31][32][33]. For high-risk neuroblastoma, surveillance imaging practices vary among institutions and the use of routine chest CT as an initial staging and surveillance tool is debatable.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the diagnostic performance of FDG PET/CT in children with osteosarcoma and Ewing sarcoma [8][9][10][11]. Presently, FDG PET/CT is not considered a standard examination in the diagnostic algorithm for these patients [12,13]. Nevertheless, in our clinical experience FDG PET/CT accurately depicts metastatic lesions from bone sarcoma both at diagnosis and at the time of relapse.…”
mentioning
confidence: 77%